Development of Magnesium Complexes for Heterofunctionalisation Catalysis - Barnes, Lydia (2024)
As concerns about climate change, pollution and resource depletion have gained an increased global awareness in the last few decades, the scientific community has recognised the need for more environmentally friendly and sustainable approaches in chemistry. This has led to research and innovation in green chemistry to develop processes and products that minimise environmental impact, reduce the use of hazardous substances, and promote the efficient use of resources. One such branch of this research is the field of earth-abundant catalysis. Over the past two decades, there has been a marked interest in the development of catalysis employing more earth-abundant metals, including the lighter first-row transition metals, as well as s- and p-block elements. The alkaline earth elements (Ae), particularly magnesium and calcium, have received a great deal of interest for their potential in more sustainable catalysis, given their high natural abundance in the Earth’s crust, resultant low cost, and low toxicity. Initial developments within Group 2 catalysis focused heavily on the heterofunctionalisation of protic reagents using the heavier congeners of the alkaline earth metals. Over the last ten years, magnesium catalysis has emerged in its own right. Reported in this thesis is the development of magnesium-catalysed heterofunctionalisation reactions, particularly with hydridic (borane and silane) reagents, to prepare synthetically relevant heteroatom-rich products. Reported in chapter two of this thesis is the investigation into two magnesium aminopyridinato complexes that are shown to be effective and selective catalysts for the hydroboration of nitriles with pinacolborane (HBpin), affording the bis(boryl) amine products with mild heating (60 °C) in high isolated yields (72−99%). Chapter three describes extensive mechanistic and kinetic studies of this hydroboration catalysis, employing reaction progress kinetic analysis of data collected from in situ continuous NMR spectroscopy. These studies suggested that the rate dependence and observed intermediates of the reaction changed significantly dependent upon the substrate employed. These studies in combination with mechanistically relevant stoichiometric reactions and control reactions, X-ray diffraction analysis of prospective catalytic reaction intermediates, and DFT calculations allowed for the proposal of a mechanism involving a unique magnesium-bound borohydride intermediate that accounts for the kinetic observations. Further studies also suggested that hidden borane species are not the primary mechanistic pathway within this catalysis. The final chapter details the extension of the observed hydroboration reactivity using catalyst 1 to further unsaturated substrates, particularly heterocumulenes. As well as attempted expansion of heterofunctionalisation catalysis with magnesium catalyst 1 to alternative hydridic substrates, other than boranes, specifically the hydrosilylation of nitriles and isocyanates. Subsequently, attempts were also made to synthesise further analogues of the aminopyridinato-stabilised magnesium complexes with a view to afford catalysts capable of achieving enhanced catalytic reactivity.